Can Basic Entrepreneurship Transform the Economic Lives of the Poor? - Oriana Bandiera; Robin Burgess; Narayan Chandra Das; Selim Gulesci; Imran Rasul; Munshi Sulaiman (Institute for the Study of Labor (IZA), 2013)
The world's poorest people lack capital and skills and toil for others in occupations that others shun. Using a large-scale and long-term randomized control trial in Bangladesh this paper demonstrates that sizable transfers of assets and skills enable the poorest women to shift out of agricultural labor and into running small businesses. This shift, which persists and strengthens after assistance is withdrawn, leads to a 38% increase in earnings. Inculcating basic entrepreneurship, where severely disadvantaged women take on occupations which were the preserve of non-poor women, is shown to be a powerful means of transforming the economic lives of the poor.
Keywords: O12; I30; D50; 330; asset transfers; capital constraints; vocational training; occupational choice; structural change; poverty